Genome‐wide association mapping of Fusarium langsethiae infection and mycotoxin accumulation in oat (Avena sativa L.). Issue 2 (8th June 2020) - Isidro‐Sánchez, Julio; D'Arcy Cusack, Kane; Verheecke‐Vaessen, Carol; Kahla, Amal; Bekele, Wubishet; Doohan, Fiona; Magan, Naresh; Medina, Angel
Abstract: Fusarium langsethiae is a symptomless pathogen of oat panicles that produces T‐2 and HT‐2 mycotoxins, two of the most potent trichothecenes produced by Fusarium fungi in cereals. In the last few years, the levels of these mycotoxin in oat grain has increased and the European commission have already recommended a maximum level for of 1000 μg kg −1 for unprocessed oat for human consumption. The optimal and most sustainable way of combating infection and mycotoxin contamination is by releasing resistant oat varieties. Here the objective was to determine if we could identify any genomic loci associated with either the accumulation of F. langsethiae DNA or mycotoxins in the grain. In each of two years, field trials were conducted wherein 190 spring oat varieties were inoculated with a mixture of three isolate of the pathogen. Mycotoxins were quantified using liquid chromatography–tandem mass spectrometry. Varieties were genotyped using 16, 863 genotyping by sequencing markers. Genome‐wide association studies associated 5 SNPs in the linkage group Mr06 with T‐2 + HT‐2 mycotoxin accumulation. Markers were highly correlated, and a single QTL was identified. The marker avgbs_6K_95238.1 mapped within genes showing similarity to lipase, lipase‐like or lipase precursor mRNA sequences and zinc‐finger proteins. These regions have previously been shown to confer a significant increase in resistance to Fusarium species.